Relationship of Rock Geomechanics and Coal Mine Slope Safety Factor in South Sumatra Region, Indonesia - Nofrohu Retongga; Rio Bagas Saputa; Friska Agustin; Rizky Syaputra; Muhammad Haikal Razi; Atikah Zahidah; Efrat N Nainggolan (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2023)
The research location is in the coal mine area South Sumatera region, Indonesia. This study aims to determine the geomechanics relationship of the rock which includes the physical properties of the rock: bulk density, and mechanical properties of the rock (shear strength), cohesion and internal shear angle to the safety factor of the coal mine slopes in the study area. Field research is carried out by observing and measuring directly in the field in the following ways: (a) Measuring slope azimuth, slope, dip direction and slope height and width using a measuring tape and geological compass. (b) Rock description based on physical characteristics (megascopic) and rock sampling for testing the physical and mechanical properties of the rock in the laboratory. (c) Observing the general condition of water from rock slopes (dry, moist, watery, wet or flowing) and slope vegetation. 2. Cohesion values and internal shear angles are secondary data obtained from PT. X which has been analyzed in the laboratory. 3. Slope modeling was carried out using Rocscience Slide software. This shows that the smaller the rock density value, the greater the rock cohesion value. The greater the cohesion value of the rock, the smaller the value of the shear angle on the rock. The smaller the value of the shear angle in the rock, the greater the value of the safety factor of the rock slope.